DEVELOPMENT OF HYDRAULIC COURSE E-MODULES TO INCREASE STUDENTS’ LEARNING INTEREST MECHANICAL ENGINEERING EDUCATION - Siman; Keysar Panjaitan; Selamat Riadi; Budi Harto (International Journal of Innovative Technologies in Social Science, 2022)
The development of printed module teaching materials in the form of hard copies into electronic-based modules with an android system or better known as Android-based E-Modules, with this electronic media it can attract students’ interest in reading because it makes it easier for students without connecting to the internet continuously. This electronic module can also help students study independently and is a good choice for developing a module. Electronic modules are innovative media that can increase interest in learning. Digital E-Module development uses a research and development (R&D) approach, which is a process used to develop and validate products. Data collection techniques in validating learning material products are carried out by distributing questionnaires. This research was designed in three stages, namely (1) Research in the form of planning and formulation of learning objectives. (2) Development in the form of making E-Modules (3) Formative evaluation and revision by material experts, media experts, and learning design experts as well as one-to one evaluation, small group, and field trial. With these three stages of research and development, it is hoped that the resulting E-Module is feasible to implement and can attract students’ learning interest to produce student knowledge in hydraulics not only in the field of education but also in the industrial sector.